THE INFLUENCE OF SERVICE QUALITY, PROMOTION AND CUSTOMER VALUE TOWARDS CUSTOMER SATISFACTION AND ITS EFFECT ON CUSTOMER LOYALTY IN TOURISM INDUSTRY PRIOR TO COVID-19 PANDEMIC - Randy Rachmadiary Dharma; Aam Bastaman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Prior to Covid-19 pandemic tourism industry has grown rapidly in Indonesia. It becomes one of most important industry to support Indonesia sustainable economy. Marketing plays a crucial role in making the tourism industry attain its objective. However, identification of the key success factors in tourism industry has to be determined. The purpose of this research is to analyses the influences of Service Quality, Promotion and Customer Value towards Customer Satisfaction and its effects on Customer Loyalty in tourism industry. The research took place in the Old Jakarta tourism area. The samples of this research are 400 Sample of domestic tourists. The results of the analysis showed that Service Quality, Promotion and Customer Value have positive influence and significant toward Customer Satisfaction. Likewise, Service Quality, Promotion and Customer Value have positive and significant influence toward Customer Loyalty directly and indirectly through mediating of Customer Satisfaction. Further, Customer Satisfaction has positive influence and significant toward Customer Loyalty. Theoretical implications and suggestions for future research in tourism industry have been elaborated at the end of this study.